Mechanically toughened EMI shielding natural rubber composite in microwave frequency bands. (28th May 2021) - Amutha Jeevakumari, S. A.; Mothilal, T.; Ramesh, G.; Arun Prakash, V. R.
ABSTRACT: Mechanically toughened high electromagnetic interference (EMI) shielding natural rubber composite material was prepared and characterised. The aim of this investigation was to reveal the role of adding cobalt nanowire and conductive graphene nanoplatelet in toughening and EMI shielding effectiveness of rubber composite in microwave bands (E, F, I and J). The composites were prepared using two roll-mill and cured at 150 ο C. The mechanical and EMI shielding behaviour was measured following ASTM standards. The addition of graphene nanoplatelet improved the toughness and skin effect of rubber, whereas cobalt nanowire improved the magnetic permeability. A highest EMI shielding of −17.6 dB in absorption and −20 dB in reflection at 18 GHz was observed for the composite made of graphene nanoplatelet and cobalt nanowire of 3 and 8phr. These mechanically toughened promising EMI shielding composite materials could be used as EMI filters and electromagnetic wave absorbers in antennae application with good toughness.